ECG viewed using Grayscale Patterns - S. Asirvadam, Vijanth; Seth Pisal, Kauv; Lila Iznita, Izhar; Noor Anis, A.M.Khuzi (Universiti Malaysia Perlis, 2010)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.